Risk Factors for the Incidence of ARI in Toddlers in Maubeli Village Kefamenanu City District North Central Timor Regency in 2022 - Metkono, Anjelina; Adu, Apris A; Landi, Soleman (Timorese Journal of Public Health, 2024)
Acute Respiratory Infection (ARI) is a type of disease that attacks the respiratory tract and usually attacks children under five because their immune system is still strong. According to some experts, the cause of this is because toddlers have weak immune systems so they are susceptible to disease. In 2021, there will be 2,212 cases of ARI in toddlers in TTU. The Sasi Health Center is the highest contributor to ARI cases in toddlers in TTU with a total of 578 cases. Data from the Sasi Health Center reported that the Maubeli Village is one of several other villages that contribute to the incidence of ARI in toddlers with a total of 108 cases. This study aims to identify factors associated with the incidence of Acute Respiratory Infections (ARI) in children under five in Maubeli Village, Kefamenanu City District, TTU Regency. This quantitative study with a cross-sectional approach involved 82 children under five as samples, selected through simple random sampling. Data analysis using the chi-square test showed that maternal knowledge (p=0.008), type of cooking fuel (p=0.017), and waste-burning behavior (p=0.030) had significant associations with ARI incidence. Meanwhile, immunization status, kitchen location, and family smoking behavior did not show significant associations. This study recommends improving maternal knowledge about ARI prevention, such as avoiding taking children to the kitchen while cooking, not using firewood as cooking fuel, and refraining from burning waste in residential areas.